Growth and reproductive performance of African giant catfish, Heterobranchus longifilis Valenciennes 1840 broodstock on ascorbic acid supplementation - adebayo, olabode thomas; Fawole, Femi John (Indian Journal of Fisheries, 2012)
This study was conducted to determine the effects of different levels of ascorbic acid supplementation on growth, reproductive performance and larval quality of Heterobranchus longifilis female broodstock fishes. Five diets were formulated incorporating ascorbic acid at levels of 0 (control), 50, 100, 150 and 200 mg kg-1. Fish averaging 700 + 2.84 g were randomly fed with the experimental diets for 8 weeks. Fish fed with control diet had lower weight gain than fish fed with ascorbic acid supplemented diets (p>0.05). The total percentage weight gain and specific growth rate in all treatments were significantly different (p<0.05). The best feed gain ratio and protein efficiency ratio was recorded in 150 and 200 mg kg-1 ascorbic acid. The percentage fertilization and hatchability in all the treatments were significantly different. The best percentage fertilization and hatchability was recorded in 200 mg kg-1 ascorbic acid diet. Diet supplemented with 150 mg kg-1 ascorbic acid performed best in terms of weight of eggs and fecundity than all other treatments. The percentage survival of the progeny was also highest in broodstock fed with diet supplemented with 150 mg kg-1 ascorbic acid. Based on the results of this study, we suggest that ascorbic acid needs to be supplemented at 150-200 mg kg-1 in the diet of female Heterobranchus longifilis broodstock.